Snoopy, come home [videorecording (DVD)] - Schulz, Charles M. (Charles Monroe), 1922-2000; Sherman, Richard M., 1928-2024; Sherman, Robert B. (Peanuts movies., 2015)
Feature-length animated film featuring the Peanuts gang, Charlie Brown, Linus, Lucy, Snoopy, and the rest, made back in the early '70s when they were still groovin' to Vince Guaraldi's jazz score.